Three-in –One Live-In Program: Building University Students’ Soft Skills: Building University Students’ Soft Skills - Yenny Hartanto (Politeknik Ubaya, 2020)
This study aimed to answer the following questions: “what are the dominant soft-skills owned by the students of Business English study program”; “what are the most difficult soft-skills for the students during the implementation of three-in-one live-in program?”. This study used a qualitative descriptive survey approach. Moreover, the data analysis used content analysis techniques. Source of data of this study were 21 university students whose majoring in Business English study program from batch 2016 1nd 2017. The findings were that dominant soft skills was adaptation (average score was 3.9), while discipline and communication were the two most difficult soft-skills. (average score was 3.7 for each). This paper contributes to the implementation of soft skills within the higher education program called 3-in-1 live-in by directly involving students and the lecturers in the field continually.